Transforming Learning with Web-based Interactive Digital Books to Improve Student Learning Outcomes - Muhammad Hairil; Muhammad Syabrina; Rahmat; arif dian pratama (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
Environmental awareness is a crucial aspect of education, particularly at the elementary level, where students begin to develop an understanding of their surroundings. This research aims to assess the feasibility and effectiveness of the interactive book Lihat Sekitar as a thematic learning medium based on environmental education for elementary school students. The study employs the Research and Development (R&D) method to develop and evaluate the teaching material. Various data collection techniques are utilized, including observations, interviews within the school environment, and questionnaires to assess student responses. The findings indicate that Lihat Sekitar is a feasible and engaging learning medium that effectively enhances students' understanding of environmental themes. The interactive features of the book encourage active participation and improve learning outcomes. The student responses, collected through questionnaires, show high levels of interest and motivation in using the book as a learning resource. These results suggest that integrating interactive and thematic approaches in elementary education can foster a deeper connection between students and their environment. This study highlights the importance of innovative teaching materials in promoting environmental literacy and suggests that Lihat Sekitar has strong potential for broader implementation in elementary education settings.